2008
DOI: 10.1088/0022-3727/41/17/175414
|View full text |Cite
|
Sign up to set email alerts
|

Growth and dielectric properties of tetragonal ZrO2films by limited reaction sputtering

Abstract: Recently, crystallized gate dielectrics have attracted considerable interest due to their high performance in dielectric properties. We investigated the growth of crystalline ZrO2 films prepared on Si (1 0 0) by the limited reaction sputtering system under different growth temperatures from 400 to 700 °C. The structural characteristics of the samples were studied by x-ray diffraction, reflection high-energy electron diffraction and atomic force microscopy, respectively, which provide a solid identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…214 To obtain high-k ZrO 2 films by stabilizing the tetragonal structure, Zhou et al reported the epitaxial growth of ZrO 2 films on Si(100) by using limited reaction dc-sputtering at several growth temperatures (400−700 °C). 120 Different from the traditional sputtering technique, for limit reaction sputtering, the metal sputtering and oxidation deposition processes are separated. During the growth process the chamber is filled with Ar as the sputter enhancing gas and O 2 as the reactive gas (for Zr metal disc oxidation) in a low concentration of 2%, and the total sputtering pressure is held at 5 mTorr.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…214 To obtain high-k ZrO 2 films by stabilizing the tetragonal structure, Zhou et al reported the epitaxial growth of ZrO 2 films on Si(100) by using limited reaction dc-sputtering at several growth temperatures (400−700 °C). 120 Different from the traditional sputtering technique, for limit reaction sputtering, the metal sputtering and oxidation deposition processes are separated. During the growth process the chamber is filled with Ar as the sputter enhancing gas and O 2 as the reactive gas (for Zr metal disc oxidation) in a low concentration of 2%, and the total sputtering pressure is held at 5 mTorr.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Generally, monoclinic and amorphous ZrO 2 films have similar dielectric constants (∼22); however, theoretical simulations suggest that k might be increased to 35–50 for cubic or tetragonal ZrO 2 films . To obtain high- k ZrO 2 films by stabilizing the tetragonal structure, Zhou et al reported the epitaxial growth of ZrO 2 films on Si(100) by using limited reaction dc-sputtering at several growth temperatures (400–700 °C) . Different from the traditional sputtering technique, for limit reaction sputtering, the metal sputtering and oxidation deposition processes are separated.…”
Section: High-k Dielectric Materialsmentioning
confidence: 99%
“…Generally, ZrO 2 films have been fabricated using vacuum-based deposition routes such as sputtering, chemical vapor deposition, and atomic layer deposition [16][17][18]. Alternatively, a sol-gel route has advantages such as simplicity and cost-effectiveness in processing, controllability of diverse chemical compositions, and applicability to large-area devices [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, tetragonal ZrOz and HfD z , attract much interests in potential application, due to their good dielectric properties [2]. To improve the interface performance between the gate insulator and Si, we developed a novel sputtering technique named "limited reaction sputtering" [3] Compared to conventional sputtering techniques, the Ar and Oz gases are introduced into different chambers, respectively, the metal sputtering and oxidation deposition processes are separated, as shown in Fig.l. Thus, the plasma radiation and the oxygen atom ions with high energy derived from plasma on Si substrate are The thickness of as-prepared films were measured by Surface Profilemeter (Dektak3 ST).…”
Section: Introductionmentioning
confidence: 99%